2010
DOI: 10.1089/acm.2009.0645
|View full text |Cite
|
Sign up to set email alerts
|

Chair Massage for Treating Anxiety in Patients Withdrawing from Psychoactive Drugs

Abstract: Within the clinical context of this study, chair massage was more effective that relaxation control in reducing anxiety. Further investigation of chair massage as a potential nonpharmacologic adjunct in the management of withdrawal related anxiety is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Black and colleagues [25] performed the first controlled study of chair massage for anxiety in 82 inpatients withdrawing from alcohol, cocaine, and opiates. Patients were randomised to three days of chair massage or a relaxation control condition.…”
Section: Resultsmentioning
confidence: 99%
“…Black and colleagues [25] performed the first controlled study of chair massage for anxiety in 82 inpatients withdrawing from alcohol, cocaine, and opiates. Patients were randomised to three days of chair massage or a relaxation control condition.…”
Section: Resultsmentioning
confidence: 99%
“…It is also worth mentioning that other CAM modalities, for which no SRs exist, show promise for various types of addictions. For instance, preliminary evidence supports the effectiveness of massage as an adjunct to traditional medical detoxification for alcohol, psychoactive drugs and nicotine …”
Section: Discussionmentioning
confidence: 99%
“…For instance, preliminary evidence supports the effectiveness of massage as an adjunct to traditional medical detoxification for alcohol, psychoactive drugs and nicotine. [41][42][43] In light of these analyses, it is important to mention the risk-benefit balance of CAM. The majority of therapies in question have a good safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…27 An RCT of a 20-minute seated massage in patients withdrawing from psychoactive drugs found significant reduction in anxiety. 28 A nonrandomized controlled study of a 20-minute seated massage in young adult psychiatric inpatients found significantly reduced self-reported anxiety and resting heart rate. 29 A larger literature reports benefits following full-body massage in a variety of patient populations and conditions: RCTs of full-body massage in patients report significantly decreased pain and improved function in patients with chronic low back pain; 30 significantly reduced pain, anxiety, and tension in postoperative cardiac patients; 31 significantly increased heart rate variability and improved mood in breast cancer survivors with cancer-related fatigue; 32 significantly reduced pain, increased muscle relaxation, and improved mood in hospice inpatients with metastatic bone pain; 33 significantly reduced depression in patients with breast cancer; 34 significantly decreased physical discomfort and fatigue 35 and perceived stress in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%